THE EFFECT OF ENTREPRENEURIAL ORIENTATION ON CLOTHING-LINE SMES PERFORMANCE IN TANAH ABANG DURING COVID-19 PANDEMIC - Utama, Louis (Graduate Program of Universitas Tarumanagara, 2023)
This study aimed to determine the effect of Creativity and Innovation, Risk Taking, Proactivity, and Autonomy on the Performance of clothing-line SMEs. This data was collected from 55 responders who owned clothing-line SMEs in Tanah Abang, Central Jakarta, from October 2021 to December 2021. The sampling technique that has been used is non-probability sampling with the purposive sampling method and data collection was carried out using a Likert scale questionnaire. This research uses Smart Partial Least Square (PLS) software version 3.0 to analyze. Overall, the results of this study are that Creativity, Innovativeness, and Proactiveness have an influence on the Performance of clothing-line SMEs in Tanah Abang, Central Jakarta, during the Covid-19 pandemic, while Risk Taking and Autonomy has no effect on the Performance of clothing-line SMEs in Tanah Abang, Central Jakarta in During the Covid-19 pandemic.